Referee decision making in a video-based infraction detection task: Application and training considerations - MacMahon, C.; Starkes, J.; Deakin, J. (International Journal of Sports Science and Coaching, 2007)
This study addressed factors that influence referee decision making in basketball. Four different groups of basketball officials were shown video clips testing their ability to detect fouls and violations (infractions). In a knowledge-priming condition, referees were given a rules test before infraction detection. In an infraction-priming condition, referees were instructed to focus on defensive fouls. The results did not show clear effects of knowledge or infraction priming. This implies that neither a pregame review of the rules or league recommendation, nor the common coach behaviour of asking a referee to focus on a particular infraction influence performance in the calls that are made. Rather, the results indicate that detecting infractions in video clips may be influenced by features of the video tool. Performance is influenced by the specific clips and their format sequencing. These findings illustrate the complexity of referee decision-making, and provide guidance for designing coaching tools for this skill. In particular, this research suggests that referee decision-making tools progress in perceptual difficulty (e.g., on-the-ball to off-the-ball infractions).